Pimeliaphilus triatomae (Acari: Pteregosomidae) used as biological control of Meccus pallidipennis (Hemiptera: Reduviidae) in laboratory conditions - ZUMAQUERO-R., JOSÉ LINO; ALEJANDRE-A., RICARDO; LINARES-F., GLADYS; CEDILLO-R., MARÍA LILIA; LÓPEZ-O., JESÚS FRANCISCO; CAICEDO-R., RICARDO (Revista Colombiana de Entomología, 2004)
Pimeliaphilus triatomae is a parasite considered entomopathogenic to triatomines; up to now, however, there is no evidence for the mortality or the action it has on its victims. For this reason the effect of parasitism was compared on the five nymphal instars and adults. as well as the eggs laid by them. The lifecycle of the mites was observed during their parasitic activity and the results obtained show a decrease in the oviposition and a prolongation in the life cycle of the infested insects with a X= of 456 days. A high mortality was obtained in ali the nymphal instars in which a rupture in the epicuticle and death by stomach evacuation was observed, after maintaining a high parasitic load. When comparing infested individuals with each control group there were significant differences (a= 0,05 ) in the mortality, oviposition and viability of the eggs.